Clinical profile of patients with non-alcoholic fatty liver disease and its association with metabolic syndrome - Pande, Abhishek; Pande, Vivek (International Journal of Advances in Medicine, 2017)
Background: Non-alcoholic fatty liver disease (NAFLD) is the accumulation of lipid, primarily in the form of triacylglycerols in individuals who do not consume significant amounts of alcohol and other known causes of steatosis, such as certain drugs and toxins, have been excluded. The rising incidence of obesity is associated with health complications. The non-alcoholic fatty liver disease is increasingly being recognized as a major cause of liver-related morbidity and mortality among 15-40% of the general population. Currently, a liver biopsy is the gold standard method for diagnosing NAFLD. Ultrasonography is relatively inexpensive and widely available in clinical settings. NAFLD is considered to be an integral part of the metabolic syndrome. The present study is designed to study the clinical profile of patients with NAFLD with varying degrees of severity as diagnosed by Ultrasonography and evaluate the relationship between the non-alcoholic fatty liver disease and the metabolic syndrome along with its individual components, as defined by the modified NCEP ATP III criteria. Methods: A cross-sectional study was conducted by Department of Medicine, NKPSIMS and LMH, Nagpur. A total of 100 cases during the study period of February 2015 to January 2016 were included and investigated for metabolic syndrome according to the NCEP ATP 3 Criteria. Results: Total of 100 cases ultrasonographically diagnosed as NAFLD were included in the study and showed 49%, 38% and 13% of cases had grade I, II, and III fatty liver respectively. On physical examination mean BMI was 27.6±4.39 kg/m2. Mean diastolic blood pressure was 92.87±6.25 and mean systolic blood pressure (mm Hg) 132.0±18.17. Out of the 100, patients with NAFLD with metabolic syndrome were 57% and without metabolic syndrome were 43%. The correlation was significant for fasting plasma glucose, diastolic blood pressure, triglycerides, high-density lipoprotein and waist circumference (p<0.05). Conclusions: From the study, it can be concluded that symptoms and signs of NAFLD are non-specific and occur later in the course of the disease hence the physician should have a high index of suspicion in order to detect NAFLD early in the course of the disease. Early detection would help not only in modifying the disease course and delaying its complications.